2013
DOI: 10.2217/fca.13.5
|View full text |Cite
|
Sign up to set email alerts
|

‘Inappropriate’ Sinus Tachycardia: Does the 100 Beats Per Min cut-off matter?

Abstract: Sinus tachycardia is commonly encountered in clinical practice and when persistent, can result in significant symptoms and impaired quality of life, warranting further evaluation. On the other hand, a growing body of epidemiological and clinical evidence has shown that high resting heart rate (HR) within the accepted normal range is independently associated with increased risk of all-cause and cardiovascular mortality. However, higher HR as a risk factor for adverse cardiovascular outcomes is frequently undera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…clozapine, olanzapine, quetiapine, risperidone, paliperidone) antipsychotics, have been associated with increased heart rate or tachycardia . A growing body of epidemiological and clinical evidence has shown that high resting heart rate even within the accepted normal range is independently associated with increased risk of cardiovascular mortality and all‐mortality causes . Thus, high resting heart rate should not be overlooked in patients treated with psychotropic drugs, particularly because pharmacological heart rate control can be easily obtained.…”
Section: Discussionmentioning
confidence: 99%
“…clozapine, olanzapine, quetiapine, risperidone, paliperidone) antipsychotics, have been associated with increased heart rate or tachycardia . A growing body of epidemiological and clinical evidence has shown that high resting heart rate even within the accepted normal range is independently associated with increased risk of cardiovascular mortality and all‐mortality causes . Thus, high resting heart rate should not be overlooked in patients treated with psychotropic drugs, particularly because pharmacological heart rate control can be easily obtained.…”
Section: Discussionmentioning
confidence: 99%
“…A small percentage of patients can have persistent sinus tachycardia without any underlying illness or structural heart disease, and are classified as having inappropriate sinus tachycardia [ 4 , 5 ]. Inappropriate sinus tachycardia is under-recognized, can be associated with debilitating symptoms and poses significant management challenges.…”
Section: When Is Tachycardia a Problem?mentioning
confidence: 99%